2003
DOI: 10.1152/ajpheart.00299.2003
|View full text |Cite
|
Sign up to set email alerts
|

Brain sodium channels and ouabainlike compounds mediate central aldosterone-induced hypertension

Abstract: Central nervous system (CNS) effects of mineralocorticoids participate in the development of salt-sensitive hypertension. In the brain, mineralocorticoids activate amiloride-sensitive sodium channels, and we hypothesized that this would lead to increased release of ouabainlike compounds (OLC) and thereby sympathetic hyperactivity and hypertension. In conscious Wistar rats, intracerebroventricular infusion of aldosterone at 300 or 900 ng/h in artificial cerebrospinal fluid (aCSF) with 0.145 M Na+ for 2 h did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 32 publications
(45 reference statements)
6
78
3
1
Order By: Relevance
“…corticosterone acetate salt-treated rats (33), as well as in Dahl S rats and SHR on high salt intake (14,32). Similar to our previous study (40), in the present study intracerebroventricular infusion of Na ϩ -rich aCSF increased OLC in the hypothalamus. Blockade of MR in the brain by intracerebroventricular infusion of spironolactone prevented this increase.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…corticosterone acetate salt-treated rats (33), as well as in Dahl S rats and SHR on high salt intake (14,32). Similar to our previous study (40), in the present study intracerebroventricular infusion of Na ϩ -rich aCSF increased OLC in the hypothalamus. Blockade of MR in the brain by intracerebroventricular infusion of spironolactone prevented this increase.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, intracerebroventricular infusion of aldosterone at low rates increases brain OLC and blood pressure (BP) (12,23), particularly when combined with small increases in CSF [Na ϩ ] (23). Blockade of brain OLC prevents intracerebroventricular aldosterone-induced sympathetic hyperactivity and hypertension (40). Increasing CSF [Na ϩ ] by intracerebroventricular infusion of Na ϩ -rich artificial CSF (aCSF) elicits sympathoexcitatory and pressor responses in a number of rat strains (21,22,25,38).…”
mentioning
confidence: 99%
“…It has also been reported that central administration of aldosterone appears to depend on the MR-ENaC-ouabain pathway and, ultimately, AT 1 receptor stimulation. 37 The sympathoexcitatory and pressor responses to central infusion of aldosterone and Na + -rich aCSF can be prevented by central infusion of the sodium channel blocker benzamil or an ouabain blocker, 27,38 and the pressor responses elicited by central infusion of aldosterone or ouabain can be blocked by an AT 1 blocker. 27,39 In the RVLM, microinjection of an ouabain-like compound 40 or angiotensin II 21 elicits a pressor response and sympathoexcitation.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, 36,39 aldosterone in the brain causes ouabain production and oxidative stress, which in turn stimulates sympathetic outflow in the central nervous system. Our results suggest that aldosterone depolarized bulbospinal RVLM neurons directly and that ENaCs are involved in this action.…”
Section: Effect Of Enac On Bulbospinal Neurons In the Rvlmmentioning
confidence: 95%
“…22,34,35 Wang et al 36 showed the presence of ENaC in the choroid plexus and the ependyma of the anteroventral third ventricle, and reported that intracerebroventricular infusion of aldosterone increased blood pressure and intracerebroventricular infusion of benzamil blocked this increase. To our knowledge, there are no reports that have indicated the existence of ENaCs in bulbospinal RVLM neurons.…”
Section: Effect Of Enac On Bulbospinal Neurons In the Rvlmmentioning
confidence: 99%